Transcriptional analysis of genes involved in nodulation in soybean roots inoculated with Bradyrhizobium japonicum strain CPAC 15 - Barros de Carvalho, Gesiele Almeida (BioMed Central, 2013)
BACKGROUND: Biological nitrogen fixation in root nodules is a process of great importance to crops of soybean [Glycine max (L.) Merr.], as it may provide the bulk of the plant’s needs for nitrogen. Legume nodulation involves several complex steps and, although studied for many decades, much remains to be understood. RESULTS: This research aimed at analyzing the global expression of genes in soybean roots of a Brazilian cultivar (Conquista) inoculated with Bradyrhizobium japonicum CPAC 15, a strain broadly used in commercial inoculants in Brazil. To achieve this, we used the suppressive subtractive hybridization (SSH) technique combined with Illumina sequencing. The subtractive library (non-inoculated x inoculated) of soybean roots resulted in 3,210 differentially expressed transcripts at 10 days after inoculation were studied. The data were grouped according to the ontologies of the molecular functions and biological processes. Several classes of genes were confirmed as related to N(2) fixation and others were reported for the first time. CONCLUSIONS: During nodule formation, a higher percentage of genes were related to primary metabolism, cell-wall modifications and the antioxidant defense system. Putative symbiotic functions were attributed to some of these genes for the first time.